Relaxin as a Therapeutic Target for the Cardiovascular Complications of Diabetes - Ng, Hooi Hooi; Leo, Chen Huei; Parry, Laura J.; Ritchie, Rebecca H. (Frontiers in Pharmacology, 2018)
Cardiovascular complications are the major cause of mortality in patients with diabetes. This is closely associated with both macrovascular and microvascular complications of diabetes, which lead to organ injuries in diabetic patients. Previous studies have consistently demonstrated the beneficial effects of relaxin treatment for protection of the vasculature, with evidence of antioxidant and anti-remodeling actions. Relaxin enhances nitric oxide, prostacyclin and endothelium-derived hyperpolarization (EDH)-type-mediated relaxation in various vascular beds. These effects of relaxin on the systemic vasculature, coupled with its cardiac actions, reduce pulmonary capillary wedge pressure and pulmonary artery pressure. This results in an overall decrease in systemic and pulmonary vascular resistance in heart failure patients. The anti-fibrotic actions of relaxin are well established, a desirable property in the context of diabetes. Further, relaxin ameliorates diabetic wound healing, with accelerated angiogenesis and vasculogenesis. Relaxin-mediated stimulation of vascular endothelial growth factor (VEGF) and stromal cell-derived factor 1-α, as well as regulation of metalloproteinase expression, ameliorates cardiovascular fibrosis in diabetic mice. In the heart, relaxin is a cardioprotective molecule in several experimental animal models, exerting anti-fibrotic, anti-hypertrophy and anti-apoptotic effects in diabetic pathologies. Collectively, these studies provide a foundation to propose the therapeutic potential for relaxin as an adjunctive agent in the prevention or treatment of diabetes-induced cardiovascular complications. This review provides a comprehensive overview of the beneficial effects of relaxin, and identifies its therapeutic possibilities for alleviating diabetes-related cardiovascular injury.